Construction of a DNA Vaccine Using Glycoprotein Gene and Its Expression Towards Increasing Survival Rate of KHV-Infected Common Carp (Cyprinus carpio) - Nuryati, Sri; Alimuddin, Alimuddin; Sukenda, Sukenda; Soejoedono, Retno Damayanti; Santika, Ayi; Pasaribu, Fachriyan Hasmi; Sumantadinata, Komar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
Deoxyribonucleic acid (DNA) vaccine has recently been developed as an alternative vaccine against virus infection.This study was the first step of DNA vaccine development to protect cyprinids including common carp (Cyprinuscarpio) and fancy koi (Cyprinus carpio) from KHV (koi herpesvirus) infection in Indonesia. One of KHV glycoproteingenes, i.e. glycoprotein (GP) was ligated with Japanese medaka (Oryzias latipes) â-actin promoter to generatepAct/GP as a DNA vaccine. Fourty fish in body weight of 10-15 g/fish were individually injected by pAct/GP intomuscle in different dosage of 2.5 μg, 7.5 μg and 12.5 μg/100 μl phosphate buffer saline. Total RNA was extractedfrom the 12.5 μg of pAct/GP-injected fish muscle at 24, 48 and 67 hours post-injection to analyze GP expression byRT-PCR method. Potential of pAct/GP as DNA vaccine was examined by injecting KHV into the 30-days-vaccinatedfish. Both of possitive and negative control fish group were not vaccinated. Possitive control fish group wereinjected with KHV, but negative control fish group were not. KHV-challenged fish were reared for 1 month, and thedeath fish were calculated daily. Result of RT-PCR analysis showed that GP gene expression were detected at 3 dpost-injection. Expression of GP in the vaccinated fish groups helped to improve their survival rate after challengedby KHV. All of fish without DNA vaccination had dead 17 days after KHV injection. The results demonstrated thatpAct/GP had high potency to be used as a DNA vaccine against KHV infection in cyprinids.